Plasma Glucosylsphingosine in GBA1 Mutation Carriers with and without Parkinson's Disease. Issue 2 (6th November 2021) - Surface, Matthew; Balwani, Manisha; Waters, Cheryl; Haimovich, Alexander; Gan‐Or, Ziv; Marder, Karen S.; Hsieh, Tammy; Song, Linxia; Padmanabhan, Shalini; Hsieh, Frank; Merchant, Kalpana M.; Alcalay, Roy N.
ABSTRACT: Background: Biallelic mutations in the GBA1 gene encoding glucocerebrosidase cause Gaucher's disease, whereas heterozygous carriers are at risk for Parkinson's disease (PD). Glucosylsphingosine is a clinically meaningful biomarker of Gaucher's disease but could not be assayed previously in heterozygous GBA1 carriers. Objective: The aim of this study was to assess plasma glucosylsphingosine levels in GBA1 N370S carriers with and without PD. Methods: Glucosylsphingosine, glucosylceramide, and four other lipids were quantified in plasma from N370S heterozygotes with (n = 20) or without (n = 20) PD, healthy controls (n = 20), idiopathic PD (n = 20), and four N370S homozygotes (positive controls; Gaucher's/PD) using quantitative ultra‐performance liquid chromatography tandem mass spectrometry. Results: Plasma glucosylsphingosine was significantly higher in N370S heterozygotes compared with noncarriers, independent of disease status. As expected, Gaucher's/PD cases showed increases in both glucocerebrosidase substrates, glucosylsphingosine and glucosylceramide. Conclusions: Plasma glucosylsphingosine accumulation in N370S heterozygotes shown in this study opens up its future assessment as a clinically meaningful biomarker of GBA1 ‐PD. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society.